The Firm-Level Impact of the Covid–19 Pandemic : Summary of Results from Round 2 - World Bank (World Bank, Washington, DC, 2020)
The World Bank commissioned a firm-level survey to provide quantitative evidence of the impact of the Coronavirus (COVID-19) pandemic. Two rounds of data have now been collected for the months of March and May using a nationally representative World Bank survey providing information on the impact of the Coronavirus (COVID-19) pandemic. The survey includes five hundred firms spanning a wide range of industries and firm sizes, as well as the formal and informal sector. This note provides a snapshot of how the firms’ outcomes and response to the pandemic have changed between the months of March and May 2020.